006 Seizure focus prediction from seizure semiology: data-driven cortical probabilis- tic heatmaps from 4643 patients. Issue 6 (27th May 2022) - Alim-Marvasti, Ali; Romagnoli, Gloria; Pérez-García, Fernando; Geranmayeh, Fatemeh; Scott, Gregory; Shahrbaf, Sadegh; Chowdhury, Fahmida Amin; Diehl, Beate; Clarkson, Matthew; Duncan, John
Abstract : Seizure semiology is important in the evaluation of patients with drug resistant focal epilepsy to help later- alise and localise the seizure onset zone for curative resection. The localising values of initial semiology are widely variable. We created the Semiology-to-Brain Database and 3D Visualisation Tool (SVT) to objectively localise the seizure focus, from an individual-participant systematic review, as per PRISMA guidelines. This yielded 11230 localising and 2391 lateralising semiology datapoints from 4643 patients across 309 studies. We integrated SVT into the freely available 3D-Slicer software with a graphical user interface, enabling visualisations of semiologies as probabilistic cortical heatmaps. We used SVT to predict the seizure-focus for a random retrospective patient: a 28-year-old right-handed gentleman. He had nocturnal generalised seizures from age 12yrs and subsequently developed stereo- typed head and eye versions to the right, tonic left leg extension and raising of the left arm with speech arrest. Ictal scalp EEG was non lateralising and interictal EEG showed bitemporal sharp waves. MRI showed cortical dysplasia in the left superior frontal gyrus and ictal SPECT highlighted the superior more than middle frontal gyrus. After intracranial EEG, a limited resection including the supplementary motor area resulted in complete seizure-freedom (ILAE 1) for four years of follow up. We demonstrate that the SVT prediction, blinded to MRI and EEG data, is congruent with the actual resection. alijesus: alim-marvasti@nhs.net 28